Interim assessment of liver damage in patients with sickle cell disease using new non‐invasive techniques. (16th December 2016) - Drasar, Emma; Fitzpatrick, Emer; Gardner, Kate; Awogbade, Moji; Dhawan, Anil; Bomford, Adrian; Suddle, Abid; Thein, Swee L.
Summary: We explored transient elastography (TE) and enhanced liver fibrosis (ELF ™ ) score with standard markers of liver function to assess liver damage in 193 well patients with sickle cell disease (SCD). Patients with HbSS or HbSβ 0 thalassaemia (sickle cell anaemia, SCA; N  = 134), had significantly higher TE results and ELF scores than those with HbSC ( N  = 49) disease (TE, 6·8 vs. 5·3, P  < 0·0001 and ELF, 9·2 vs. 8·6 P  < 0·0001). In SCA patients, TE and ELF correlated significantly with age and all serum liver function tests (LFTs). Additionally, (weak) positive correlation was found with lactate dehydrogenase (TE: r  = 0·24, P  = 0·004; ELF: r  = 0·26 P  = 0·002), and (weak) negative correlation with haemoglobin (TE: r  = −0·25, P  = 0·002; ELF: r  = −0·25 P  = 0·004). In HbSC patients, correlations were weaker or not significant between TE or ELF, and serum LFTs. All markers of iron loading correlated with TE values when corrected for sickle genotype (serum ferritin, β = 0·25, P  < 0·0001, total blood transfusion units, β = 0·25, P  < 0·0001 and LIC β = 0·32, P  = 0·046). The exploratory study suggests that, while TE could have a role, the utility of ELF score in monitoring liver damage in SCD, needs further longitudinal studies.